Comparison of methods for isolating fungal DNA - Galliano, Ilaria; Daprà, Valentina; Zaniol, Elena; Alliaudi, Carla; Graziano, Elisa; Montanari, Paola; Calvi, Cristina; Bergallo, Massimiliano (Practical laboratory medicine, 2021)
The main aim of this work was to compare the methods of DNA isolation in the moulds of genus Mucorales with special regard to the amount and purity of the DNA acquired. The acquired DNA was then amplified by specific real-time PCR. Five DNA extraction procedures were carried out in a Class 2 Biosafety cabinet in a dedicated room with suitable biosafety precautions and appropriate biowaste disposal methods. A total of 6 Mucorales clinical strains were used. From the viewpoint of concentration and purity, methods A shown abundant amount of fungal DNA whereas methods E report a pure fungal DNA with R260/280 of 1.7 near the optimal 1.8. The DNA quantity reach statistically difference at ANOVA test with p value 0.0005 Overall, the E method was the most efficient method in the extraction of DNA from fungal cultures compared to the other methods considering time, cost, technical expertise, and instrumentation. Use of this assay will allow researchers to obtain DNA from fungi quickly for use in molecular assays